APLICACIÓN DE UNA METODOLOGÍA PARA EVALUAR LA AGRESIVIDAD DEL AGUA HACIA ESTRUCTURAS DE CONCRETO - Vargas, Asdrúbal (2011)
The chemical characteristics of surface and groundwater were analyzed near the main structureof the Toro III hydroelectric project . The reaction of water with concrete was determinated using the index ofLangelier and Ryznar, which can be used to describe the aggressiveness of water over structures of concrete andcity monuments constructed with sensible materials. Investigation of chemical characteristics and water aggres-siveness to concrete is necessary in projects where the water is frequently in contact with the walls of the tun-nel, similar to the Toro III project. The water samples from embalse Toro II show high concentrations of majorions; the samples from Gemelas and Flor Creek have negative values of Langelier index (< -1,5). All these sam-ples are aggressive to concrete. The water samples collected in Flor creek have very low concentrations of majorions as comparedto the rest of the samples.